Meaning and function in the theory of consumer choice: dual selves in evolving networks - Carsten Herrmann-Pillath (Frankfurt School of Finance & Management, 2010)
Building on the philosophy of Charles Sanders Peirce, recent advances in biosemiotics have resulted into a concise framework for the analysis of signs in living systems. This paper explores the potential for economics and shows how biosemiotics can integrate two different research agendas, each of which are also connected with biological theories, namely neuroeconomics and the theory of networks. I introduce the triadic conceptual framework established by Peirce which distinguishes between object, sign and interpretant and the corresponding causal forces in evolving hierarchical systems. This framework is used to systematize recent results of neuroeconomics in the form of the dual selves approach, following early contributions of James Coleman, partitioning the individual into the acting self and the object self. This distinction implies that there is a fundamental information asymmetry between the two selves. Against this background, the semeiotic process is an information generating and processing dynamics, which is driven by the internal selection of classificatory schemes of actions chosen and the population level dynamics of sign selection, with mimetic behavior as a driver. This can be further analyzed by means of the theory of signal selection. A central insight is that the internal information gap between acting self and object self implies a systematic role of sign processing in social networks for any kind of consumer choice. I exemplify my approach with empirical references to food consumption as a most universal and simple form of consumer choice.
Keywords: B52; D80; Q57; 330; consumer choice; biosemiotics; dual selves; networks; signal selection; Konsumentenverhalten; Neuroökonomie; Soziales Netzwerk; Semiotik; Bioökonomik; Theorie; Nahrungsmittelkonsum